2018
DOI: 10.5539/ijbm.v13n2p167
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spiritual Leadership in Reducing Bullying Behavior: A Study on the Industrial Companies in Egypt

Abstract: The objective of the research is to identify the role of Spiritual Leadership (SL) in reducing Bullying Behavior (BB) at the industrial companies in Egypt. The research community consists of all the employees at the industrial companies (the iron and steel sector, the construction sector, the food industry, the spinning and weaving sector and the chemical industries sector) in Sadat city in Egypt. Due to time and cost constraints, the researcher adopted a sampling method to collect data for the study. The appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…On the other hand, Nafei (2018) researched on bullying supervision in companies in Sadat City of Egypt. He found that verbal bullying was rampant in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Nafei (2018) researched on bullying supervision in companies in Sadat City of Egypt. He found that verbal bullying was rampant in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…If the module of an example of success was added to the course, this would give participants a clear picture after sharing successful experiences with other individuals and lecturers. As a result, the principles of spiritual leadership could be utilized in educational institutions efficiently, as stated in the study by Nafei (2017) who suggested that a manager with spiritual leadership would not only make employees work happily, full of commitment, but would also create a good atmosphere in the organization that could improve performance. Hence, this helped the members to build good relationships with each other, and reduce bullying behavior in the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual leadership can be applied to the changing situations of both organizations and the world, especially since world society had been greatly affected by the COVID-19 pandemic (Admad et al, 2021). As a result, spiritual leadership has been researched in numerous dimensions, including education (Evalyna & Wibawa, 2020;Nurabadi et al, 2021;Usman et al, 2021), business (Wang et al, 2019;Hunsaker & Jeong, 2020;Cho, 2021;Widyanti et al, 2021), the industrial area (Torkamani, 2015;Nafei, 2017;Wang et al, 2021), public health/nursing (Rosa & Ancok, 2020;Ahmad et al, 2021), religion (Nwadike, 2015) and the community (Junaedi & Waruwu, 2020). Moreover, despite the fact that the world is in crisis, spiritual leadership can positively affect the innovative behaviors of people in an organization (Widyanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However spiritual leadership has the capacity to fuel the growth of workplace spirituality, which in turn develops the spirits of employees; this reduces bullying and uncivil behavior (Ghaedi et al, 2021). Spiritual leadership with dimensions such as vision, hope, altruism, membership and meaning of work can reduce bullying behavior (Nafei, 2018). Workplace spirituality can also be one way to reduce deviant behavior at workplace (Chawla 2014; Astuti et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%